Small fiber polyneuropathy: A new therapeutic target in patients with interstitial cystitis/bladder pain syndrome? - Whitman, Wyatt; Sandberg, Maxwell; Lee, Peyton; Walker, Stephen J. (Frontiers in Urology, 2023)
Interstitial cystitis/bladder pain syndrome (IC/BPS) is a debilitating chronic disease that, based on the variable efficacy observed with most therapeutic options, is difficult to treat effectively. A more targeted patient selection process for current and emerging therapeutic options would likely help to improve outcomes. This narrative review explores small fiber polyneuropathy (SFPN) in IC/BPS as part of a larger widespread pain phenotype and as a potential therapeutic target. Because SFPN is becoming increasingly implicated in polysyndromic pain disorders (e.g., IC/BPS, chronic pelvic pain, and fibromyalgia) in which immune dysregulation is a suspected pathophysiologic etiology, continued consideration should be given to immunomodulatory therapies such as intravenous immunoglobulin (IVIg). Moreover, since the small fibers affected in SFPN continue to grow even as people age, targeted treatment may prevent further destruction and provide long-term benefits as the fibers are given time to repair. In addition to therapeutic potential, having a definitive SFPN diagnosis may provide psychological benefit in a patient population for which symptoms have historically been attributed to negative psychological factors. Finally, based on emerging data in this area, we propose consideration be given to include SFPN testing in the work-up of patients with IC/BPS that are refractory to treatments or have multiple comorbid pain syndromes since it may be an indicator of the need for alternative therapies. We believe that SFPN will play an increasingly larger role in the clinical evaluation and management of polysyndromic pain disorders, including IC/BPS.